Influence of Integrated Nutrient Management Practices On Soil Properties and Yield of Potato (Solanum tuberosum. L) in an Inceptisol of Khajura, Banke - Kafle, Kishor; Shriwastav, Chandeshwar Parsad; Marasini, Madan (International Journal of Applied Sciences and Biotechnology, 2019)
Field experiment was conducted at the research farm of Regional Agriculture Research Station (RARS), Khajura to evaluate the influence of integrated nutrient management options that could enhance the properties of soil and yield of potato under the different climatic conditions of Khajura. The experiment was started in November 2016 in randomized complete block design with different seven treatments of nutrients using Farm yard manure (FYM), Poultry manure (PM) Vermicompost (VC). Available N, P and K status in the soil increased gradually due to the application of inorganic and organic fertilizers. The plots receiving 50 % RDNPK through inorganic fertilizers and remaining 50% RDN through PM registered the highest available N, P and K status in the soil. The highest pH (6.3) content in soil was found in plots treatments with poultry manure and inorganic fertilizers. Potato plots treated with FYM and inorganic fertilizers produced higher SOM content in soil after harvest (2.38%) as compared to control plots (2.09%). The treatments integrated with FYM show less bulk density than the control plot. Organic manures treated plots produce taller plants as compared plots receiving inorganic fertilizers only. Integrated use of 50 % recommended dose of NPK through inorganic fertilizers and remaining 50% RDN through PM produced higher numbers of tubers per plot (304 tubers per plot) and total tuber yield (22.86 tha-1). Int. J. Appl. Sci. Biotechnol. Vol 7(3): 365-369